Pengembangan Usaha Ukir Temaja di Banjar Sawan, Desa Siangan Kabupaten Gianyar melalui Peningkatan Kapasitas Bidang Produksi dan Pemasaran - Made Mulia Handayani; I ketut Satria Wiradhama Sumertajaya; Ade Maharini Adiandari; Gede Sumarda; Made Artana (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
Banjar Sawan is famous for its carving business. One of the carving businesses that can be said to be the pioneering business for carving business in Banjar Sawan is the Temaja carving business. This carving business is engaged in the Balinese stile carving business. This carving business is capable of making various types of carvings. The results of this carving business are sold directly to customers who come to Banjar Sawan. This carving business has been around for many years, which is a legacy from their ancestors in Banjar Sawan. The problems faced by partners include not having a wood sanding machine to speed up the production process, not having carried out promotions using social media such as Instagram or Facebook. In addition to increasing market access, the Temaga carving business needs to make improvements in the areas of production management and financial management, so that the pasek carving business can develop better. The resulting outputs are in the form of articles in national seminar proceedings, articles in print media, videos of activity implementation, increased production capacity and quality by 10%, business management skills both in the field of promotion and financial management and being able to make simple bookkeeping. Through meetings with the owners of the copper carving business, it was agreed that programs would be carried out to improve the quality of production and sales. These programs are carried out using training methods, mentoring, direct practice, monitoring and evaluation. The programs that have been agreed upon in the PKM will be carried out for two months.